Suicides and Suicidal Ideation During the Perinatal Period: Clinical and Demographic Data by Xenophon, Panagiotis, Eirini, Christiana, and Areti (2022) - Alruwaili, Manar (International Journal of Innovative Research in Medical Science, 2023)
The Perinatal period, encompassing pregnancy and the postpartum stage, is a critical time that significantly affects women's mental health and overall well-being. Suicides and suicidal ideation pose pressing public health concerns during this period. High-risk factors, including depression and other mental disorders such as schizophrenia, anxiety, bipolar disorder, and adjustment disorder, further emphasize the need for attention. Healthcare providers play a vital role in identifying at-risk women and connecting them with the necessary resources and mental health services.